2018
DOI: 10.1111/hae.13516
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density and associated factors in patients with haemophilia in Colombia

Abstract: Results from the present study showed that haemophilia was associated with a higher frequency of LBMD. Severity of haemophilia, haemophilic arthropathy, and elevated C-reactive protein levels was directly associated with LBMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
1
18
1
Order By: Relevance
“…Previous studies reported some discrepancies in the risk factors associated with low bone mass in patients with hemophilia in different populations. While low physical activity, HCV infection, vitamin D deficiency, BMI, arthropathy, and cigarette smoking were the possible risk factors in previous reports (4,7,11,12,14,(24)(25)(26)(27), our data proved that severity of factor VIII / IX deficiency was the most critical risk factor associated with both femoral and spinal LBM. One animal study showed that, unlike normal mice, non-bleeding mice with hemophilia had lower BMD and abnormal bone structure (26,28).…”
Section: Discussionsupporting
confidence: 45%
“…Previous studies reported some discrepancies in the risk factors associated with low bone mass in patients with hemophilia in different populations. While low physical activity, HCV infection, vitamin D deficiency, BMI, arthropathy, and cigarette smoking were the possible risk factors in previous reports (4,7,11,12,14,(24)(25)(26)(27), our data proved that severity of factor VIII / IX deficiency was the most critical risk factor associated with both femoral and spinal LBM. One animal study showed that, unlike normal mice, non-bleeding mice with hemophilia had lower BMD and abnormal bone structure (26,28).…”
Section: Discussionsupporting
confidence: 45%
“…Haemophilia patients have been shown to have lower BMD compared with the general population or healthy control group . In the present study, BMD levels of haemophilia patients were compared to those of a healthy control group, and the results were evaluated.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, according to the results of this study, the prevalence of bone density reduction in the spine and hip bones in patients with hemophilia and hepatitis was not significantly different in term of the severity of hemophilia which is not in line with the results of SossaMelo et al . (2018) [ 29 ] and Lorio et al . (2010).…”
Section: Discussionmentioning
confidence: 99%